ANALISIS EFEKTIVITAS KOLABORASI AFFILIATE MARKETING DAN CONTENT BRANDING PADA UMKM KONVEKSI ONLINE DI KECAMATAN AMBARAWA - Siti Zumatun Kumaeroh; Agus Priyadi; Priyadi; Robby Andika Kusumajaya (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study aims to analyze the effectiveness of collaboration between affiliate marketing and content branding strategies on the performance of online convection MSMEs in Ambarawa District. The method used is quantitative with a descriptive and verification approach. The research sample consisted of 35 convection MSMEs that have implemented digital marketing strategies, specifically affiliate marketing and content branding. Data were collected through questionnaires and interviews, then analyzed using multiple linear regression tests. The results showed that both affiliate marketing (X1) and content branding (X2) had a positive and significant effect on increasing sales (Y), with beta coefficient values of 0.327 and 0.514, respectively. The coefficient of determination (R²) value of 0.392 indicates that 39.2% of the variation in MSME performance is explained by these two variables. This finding confirms that the synergy between affiliate marketing and content branding is an effective strategy in improving MSME digital marketing performance. This study recommends that MSMEs strengthen the quality of content used by affiliate partners and expand their digital collaboration networks with facilitation support from the local government.